A Micro-Computed Tomography (micro-CT) Analysis of Postmenopausal Osteoporotic Rat Models Supplemented with Ficus carica - Adlina Mohammad, Norfarah Izzaty Razaly, Mohd Dzulkhairi Mohd Rani, Muhammad Shamsir Mohd Aris, Sulaiman Md Dom, Nadia Mohd Effendy (Journal of Applied Pharmaceutical Science, 2018)
Estrogen replacement therapy (ERT) is known to be effective as an anti-osteoporotic treatment for postmenopausal women but exerted many adverse effects. Ficus carica (FC) or fig is a fruit rich in antioxidants and anti-inflammatory sources that are believed to contribute to its potential as ERT alternative. This study aimed to evaluate the effects of FC supplementation on the trabecular microarchitecture of postmenopausal osteoporotic rat models. Fifty-six adult female Sprague-Dawley rats were randomly divided into groups of Sham-operated (Sham), ovariectomized control (OVX), ovariectomized with 64.5 μg/kg estrogen Premarin (ERT), ovariectomized with 50 mg/kg aqueous extract of FC (FC50), ovariectomized with 100 mg/kg aqueous extract of FC (FC100), ovariectomized with 50 mg/kg raw extract of FC (RAW50) and ovariectomized with 100 mg/kg raw extract of FC (RAW100). The treatments were given daily via oral gavage for eight weeks. After the treatment, rats were euthanized and femora were dissected out for micro-computed tomography (micro-CT) analysis. Trabecular structure of OVX femur showed significant osteoporotic deterioration in bone volume, trabecular separation, structural model index and connectivity density. ERT significantly reversed the osteoporotic-induced bone changes comparable to Sham level. RAW50 showed the best FC treatment in preserving bone microarchitecture. In conclusion, raw extraction of FC has high potential as an alternative against osteoporosis due to its high mineral contents and bioactive compounds.
Keywords: Postmenopausal osteoporosis, ovariectomy, Ficus carica, estrogen, bone microarchitecture, micro-CT.